Judgment of land ownership by young refugee Palestinian and U.S. children - Zebian, Samar (2012)
Children’s sense and reasoning about territory and land ownership may develop differently in contexts of poverty and where narratives of dispossession are a part of daily life and are of political and historical significance, as is the case in the Palestinian refugee context in Lebanon. In this study we looked at how 3- and 5-year-old refugee Palestinian and American children distribute land among neighbors disputing over an unoccupied piece of land separating their properties. Children were required to make distributive justice decisions about 4 scripted scenarios that involved a pretend conflict between different types of neighbors (rich/poor; ingroup vs. outgroup; neighbors of the same material wealth and neighbors that were either poor or rich as well as ingroup members). Both 5-year-old Palestinian and American children showed inequality aversion, favoring the poor neighbor over the rich in their distributive justice decisions. This first finding suggests that being born into poverty does not make young children more sensitive to material inequity, even if the object of dispute is of particular cultural relevance. However, a second main finding suggests that extreme circumstances potentially translate into enhanced ingroup partialities, above and beyond the universal normative trend toward inequity aversion.